PENGARUH LEVERAGE, PROFITABILITAS, DAN PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA - Ningrum, Tika Deby Aprilia; Mahroji, Mahroji (Jurnal Ilmiah Global Education, 2023)
The study aims of this research is to analyse the impact of leverage, profitability, and tax planning on earnings management. The data used in this study are secondary data derived from the financial statements of companies listed on the Indonesian Stock Exchange (BEI) for the period 2019 – 2021. The research sample used 50 companies that met the criteria of a total of 216 companies with purposive sampling methods for the sample collection of the research. Data analysis using panel data regression, this study measurement using Econometric Views 12 (EViews 12). The results of this study show that the variable leverage projected by the Debt-equity ratio (DER) has a significant negative impact on earnings management. Variable profitability projected with Return on assets (ROA) has a significant positive impact on earnings management. Tax planning variables proxied with the Tax Retention Rate (TRR) do not affect earnings management. For the company to be able to define positive policies that can maintain the sustainability of the business and can meet the expectations of shareholders in earnings management.